Fracture in the Elderly Multidisciplinary Rehabilitation (FEMuR): a phase II randomised feasibility study of a multidisciplinary rehabilitation package following hip fracture. Issue 10 (5th October 2016) - Williams, Nefyn H; Roberts, Jessica L; Din, Nafees Ud; Totton, Nicola; Charles, Joanna M; Hawkes, Claire A; Morrison, Val; Hoare, Zoe; Williams, Michelle; Pritchard, Aaron W; Alexander, Swapna; Lemmey, Andrew; et al.
Abstract : Objective: To conduct a rigorous feasibility study for a future definitive parallel-group randomised controlled trial (RCT) and economic evaluation of an enhanced rehabilitation package for hip fracture. Setting: Recruitment from 3 acute hospitals in North Wales. Intervention delivery in the community. Participants: Older adults (aged ≥65) who received surgical treatment for hip fracture, lived independently prior to fracture, had mental capacity (assessed by clinical team) and received rehabilitation in the North Wales area. Intervention: Remote randomisation to usual care (control) or usual care+enhanced rehabilitation package (intervention), including six additional home-based physiotherapy sessions delivered by a physiotherapist or technical instructor, novel information workbook and goal-setting diary. Primary and secondary outcome measures: Primary: Barthel Activities of Daily Living (BADL). Secondary measures included Nottingham Extended Activities of Daily Living scale (NEADL), EQ-5D, ICECAP capability, a suite of self-efficacy, psychosocial and service-use measures and costs. Outcome measures were assessed at baseline and 3-month follow-up by blinded researchers. Results: 62 participants were recruited, 61 randomised (control 32; intervention 29) and 49 (79%) completed 3-month follow-up. Minimal differences occurred between the 2 groups for most outcomes, including BADL (adjusted mean difference 0.5). The intervention group showed a medium-sized improvement in the NEADL relative to the control group, with an adjusted mean difference between groups of 3.0 (Cohen's d 0.63), and a trend for greater improvement in self-efficacy and mental health, but with small effect sizes. The mean cost of delivering the intervention was £231 per patient. There was a small relative improvement in quality-adjusted life year in the intervention group. No serious adverse events relating to the intervention were reported. Conclusions: The trial methods were feasible in terms of eligibility, recruitment and retention. The effectiveness and cost-effectiveness of the rehabilitation package should be tested in a phase III RCT. Trial registration number: ISRCTN22464643 ; Results.